The Role of Economic Academic Education on Entrepreneurial Behaviour - Renata Dana Niţu-Antonie; Emőke-Szidónia Feder (Amfiteatru Economic)
The study aims to identify the role played by personality characteristics on entrepreneurial intentions and resultant behaviours, in the case of university students with economic education. The analysis was performed on a group of undergraduate and master degree students of the Faculty of Economics and Business Administration from the West University of Timişoara. For the investigated population, empirical results indicate that: (i) personality characteristics are antecedents of behavioural characteristics depending on situational constraints that allow their expression; (ii) behavioural characteristics emerge as significant predictors of entrepreneurial intention; (iii) entrepreneurial intention is a primary forecaster of real entrepreneurial activity; (iv) the increase of educational level and study programs’ specificity, to which the investigated population belongs, guarantee for entrepreneurial awareness raising and instruction of aspirant entrepreneurs.